Eliminating false sharing - Eggers, Susan J.; Jeremiassen, Tor E. (1990)
Abstract: "The performance and scalability of bus-based, shared memory multiprocessors is limited by the amount of bus traffic. Previous studies have shown that for machines with large caches and a write- invalidate coherency protocol, most of the bus traffic stems from coherency overhead. Some of this overhead is unavoidable, a direct consequence of the true sharing activity in the program. However, for caches with multi- word cache blocks, coherency overhead can also be caused by multiple processors accessing different words in the same block, known as false sharing. This paper measures the amount of false sharing in two types of parallel applications. For some applications the amount of false sharing increases substantially as block size increases
Keywords: Parallel programming (Computer science)